Estereotipos femeninos desde la antigüedad clásica hasta el siglo XVI - Plaza Picón, Francisca del Mar; González Doreste, Dulce María; Plaza Picón, Francisca del Mar (Walter de Gruyter & Co., 2022)
The volume gathers eleven contributions on the origins, evolution and function of female models in Western culture, from Greco-Roman texts to medieval and Renaissance literature. Organized in four thematic blocks, the book intends to elucidate how misogynistic discourse and its opposite are constructed in literary and didactical works dealing with feminine archetypes